Analisis Penerapan Informasi Akuntansi Manajemen dalam Perencanaan Anggaran Pemerintah Desa - Elsa Candra Bahuwa; Mattoasi; Titi Umi Kalsum Hulopi (Transbahasa, 2026)
This study aims to analyze the application of management accounting information in improving the quality of budget planning in Permata Village, Tilongkabila District, Bone Bolango Regency. This study employed a qualitative method, with data obtained through documentation and informants involved in the village planning and budgeting processes. The analysis focused on the use of management accounting information in determining programs, establishing priorities, allocating budgets, and assessing the alignment between planned activities and the village’s financial capacity. The results showed that the application of management accounting information in budget planning was not yet optimal. Although the planning process had been conducted through village deliberations, the information used as a basis for determining program needs and budget allocations remained inadequate. This condition resulted in discrepancies between planned programs and available budgets. Several programs planned for 2025 could not be implemented due to budget limitations and budget reallocations to address more urgent needs. Therefore, the Permata Village Government needs to improve the quality of management accounting information so that it is more accurate, relevant, and consistent with the village’s financial conditions. The optimal application of such information is expected to support priority setting, improve the effectiveness and efficiency of budgeting, and ensure that planned programs can be implemented in accordance with community needs. The findings highlight the importance of integrating management accounting information into village budget planning and decision-making processes.